Closed Form Solution for a Damped Rotational Pendulum System - Alvaro H. Salas S. (Research Updates in Mathematics and Computer Science Vol. 4, 2024)
In this article, we report for the first time the analytical solution for a rotational pendulum system. Analytical expression for the period of oscillations is provided. We also derive approximate analytical solution for the damped case.